Fabrication of bacterial cellulose with high efficient loading of Ag and TiO2 nanoparticles for removing organic dyes. Issue 3 (17th July 2021) - Hu, Jinyan; Liu, Suo; Wu, Dingsheng; Pan, Dengyu; Feng, Quan
Abstract: As a new advanced oxidation technology, photocatalytic technology has broad application prospects in the field of wastewater treatment. However, in the actual use process, there will be difficulties in catalyst recovery and reuse. This article successfully prepared bacterial cellulose (BC) loaded silver and titanium dioxide nanoparticles (Ag‐plated TiO2 /BC composite pellicle) by in situ embedding method. BC not only works as the carrier to load TiO2 and Ag NPs but also adsorbs dyes to promote the reaction. As a reusable photocatalytic film, it is convenient to use and recycle in terms of testing and characterization compared with powders. The results show that Ag and TiO2 nanoparticles were closely embedded in BC. We evaluated the photocatalytic degradation performance of the catalyst on methylene blue (MB), active red X‐3B, and Rhodamine B. When the reaction time was 2 h, the dye removal rates were 71%, 68%, and 82.6%. At the same time, through the inhibition zone experiment, it was found that the material has a certain inhibitory effect on both Escherichia coli and Staphylococcus aureus . Therefore, the supported catalyst prepared by this method has the advantages of high catalytic activity, relatively stable property, easy recovery, and tailorability, making it potentially applicable in sewage post‐treatment links. Abstract : In this article, bacterial cellulose was used as a carrier, and a flexible photocatalytic material loaded with nano‐silver and titanium dioxide particles was prepared by in situ synthesis and electroless plating. Through a series of photocatalytic degradation of dyes and antibacterial experiments, it is found that the catalyst prepared in this article has excellent photocatalytic and antibacterial properties.